An Innovative Anode Interface Combination for Perovskite Solar Cells with Improved Efficiency, Stability, and Reproducibility - Meng, Wei; Xu, Junyi; Dong, Lirong; Zhang, Jiyun; Xie, Zhiqiang; Luo, Junsheng; Zhao, Baolin; Zhang, Kaicheng; Osvet, Andres; Heumüller, Thomas; Forberich, Karen; Halik, Marcus; et al. (Solar RRL, 2022)
Rational design and engineering of top interface layers with combined properties of effective passivation, high thermal- and photo-stability are effective methods to advance the commercialization of perovskite photovoltaics. Here, an innovative anode interface combination is developed based on alcohol-dispersed poly (3-hexylthiophene-2,5-diyl) (P3HT) nanoparticles as the hole transport material and chlorobenzene-dissolved trioctylphosphine oxide (TO PO) as the passivation agent. It is shown that instead of the commonly used 2D passivation ligands, TOPO-passivated perovskite films exhibit greatly improved thermal stability. Furthermore, the passivation contributes to an enhanced carrier lifetime and reduced surface trap density, yielding an improvement in the quasi-fermi-level splitting of 57 meV. To maintain surface passivation during solution processing of further layers, it is necessary to develop a hole transport layer that can be processed from orthogonal solvents. P3HT nanoparticles formulated in alcoholic media fully meet this requirement, clearly benefitting from their high vertical conductivity and extremely low contact resistance with carbon electrodes. Based on this configuration, device efficiency of up to 18.4% is demonstrated for perovskite solar cells with fully solution-processed carbon electrodes, along with significantly improved device stability and reproducibility.
CRIS-Team WoS Importer:2022-06-17

Controlling Intermediate Phase Formation to Enhance Photovoltaic Performance of Inverted FA-Based Perovskite Solar Cells - Li, Chaohui; Park, Hyoungwon; Qiu, Shudi; Streller, Fabian; Zhang, Kaicheng; Peng, Zijian; Byun, Jiwon; Tian, Jingjing; Maiti, Santanu; Xie, Zhiqiang; Dong, Lirong; Liu, Chao; et al. (ACS Energy Letters, 2024)
Formamidinium (FA)-based perovskites exhibit significant potential for highly efficient photovoltaics due to their promising optoelectronic properties and optimal bandgap. However, the undesired inactive phase arises from multiple crystal nucleation pathways formed by various intermediate phases during the film formation process, persistently accompanying it. FA-based perovskites frequently struggle to form uniform, highly crystalline films. This challenge complicates the development of reliable and highly reproducible crystallization processes for perovskites and the establishment of guidelines for controlling the α-phase formation. In this work, we investigate the role of poly(acrylonitril-co-methyl acrylate) (PAM) to simultaneously control nucleation and subsequent α-phase crystallization. This successfully demonstrates the regulation of oriented crystal growth through the creation of a PAM-PbI2 intermediate. Ultimately, PAM-modified p-i-n architecture devices obtain a promising power conversion efficiency (PCE) of 25.30%, with VOC (1.211 V), achieving 95% of the detailed balance limit. Additionally, PAM-modified devices maintain ≥90% of the initial efficiency for 1000 h under 1 sun and 65 °C operation.
CRIS-Team Scopus Importer:2024-11-22

Correction to: Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime (Nature Communications, (2024), 15, 1, (2002), 10.1038/s41467-024-46145-7) - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
Correction to: Nature Communicationshttps://doi.org/10.1038/s41467-024-46145-7, published online 05 March 2024 In this article, Junsheng Luo and Bowen Liu should have been denoted as equally contributing authors. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

Impact of 2D Ligands on Lattice Strain and Energy Losses in Narrow-Bandgap Lead–Tin Perovskite Solar Cells - Zhang, Kaicheng; Vincze, Andrej; Metwalli, Ezzeldin; Zhang, Jiyun; Liu, Chao; Meng, Wei; Zhang, Boxue; Tian, Jingjing; Heumüller, Thomas; Xie, Zhiqiang; Luo, Junsheng; Osvet, Andres; et al. (Advanced Functional Materials, 2023)
Mixed lead and tin (Pb/Sn) hybrid perovskites exhibit a great potential in fabricating all-perovskite tandem devices due to their easily tunable bandgaps. However, the energy deficit and instability in Pb/Sn perovskite solar cells (PSCs) constrain their practical applications, which renders defect passivation engineering indispensable to develop highly efficient and long-term stable PSCs. Herein, the mechanisms of strain tailoring and defect passivation in Pb/Sn PSCs by 2D ligands are investigated. The 2D ligands include electroneutral cations with long alkyl chain (LAC), iodates with relatively short alkyl chain (SAC) and their mixtures. This study reveals that LAC ligands facilitate the relaxation of tensile strain in perovskite films while SAC ligands cause strain buildup. By mixing LAC/SAC ligands, tensile strain in perovskite films can be balanced which improves solar cell performance. PSCs with admixed β-guanidinopropionic acid (GUA)/phenethylammonium iodide (PEAI) exhibit enhanced open circuit voltage and fill factor, which is attributed to reduced nonradiative recombination losses in the bulk and at the interfaces. Furthermore, the operational stability of PSCs is slightly improved by the mixed 2D ligands. This work reveals the mechanisms of 2D ligands in strain tailoring and defect passivation toward efficient and stable narrow-bandgap PSCs.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 2D ligand passivation; energy losses; lead/tin perovskite solar cells; stability; strain tailoring

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Inverse design workflow discovers hole-transport materials tailored for perovskite solar cells - Wu, Jianchang; Torresi, Luca; Hu, Manman; Reiser, Patrick; Zhang, Jiyun; Rocha-Ortiz, Juan S.; Wang, Luyao; Xie, Zhiqiang; Zhang, Kaicheng; Park, Byung-Wook; Barabash, Anastasia; Zhao, Yicheng; et al. (Science, 2024)
The inverse design of tailored organic molecules for specific optoelectronic devices of high complexity holds an enormous potential but has not yet been realized. Current models rely on large data sets that generally do not exist for specialized research fields. We demonstrate a closed-loop workflow that combines high-throughput synthesis of organic semiconductors to create large datasets and Bayesian optimization to discover new hole-transporting materials with tailored properties for solar cell applications. The predictive models were based on molecular descriptors that allowed us to link the structure of these materials to their performance. A series of high-performance molecules were identified from minimal suggestions and achieved up to 26.2% (certified 25.9%) power conversion efficiency in perovskite solar cell
CRIS-Team Scopus Importer:2025-02-04

Modulating Trapping in Low-Dimensional Lead–Tin Halides for Energy-Efficient Neuromorphic Electronics - Chen, Lijun; Saleh, Saad; Tavormina, Filippo; Di Mario, Lorenzo; Li, Jiaxiong; Xie, Zhiqiang; Masciocchi, Norberto; Brabec, Christoph J.; Koldehofe, Boris; Loi, Maria Antonietta (Advanced Materials, 2025)
Metal halide perovskites have drawn great attention for neuromorphic electronic devices in recent years, however, the toxicity of lead as well as the variability and energy consumption of operational devices still pose great challenges for further consideration of this material in neuromorphic computing applications. Here, a 2D Ruddlesden-Popper (RP) metal halides system of formulation BA2Pb0.5Sn0.5I4 (BA = n-butylammonium) is prepared that exhibits outstanding resistive switching memory performance after cesium carbonate (Cs2CO3) deposition. In particular, the device exhibits excellent switching characteristics (endurance of 5 × 105 cycles, ON/OFF ratio ≈105) and achieves 90.1% accuracy on the MNIST dataset. More importantly, a novel energy-efficient content addressable memory (CAM) architecture building on perovskite memristive devices for neuromorphic applications, called nCAM, is proposed, which has a minimum energy consumption of ≈0.025 fJ bit/cell. A mechanism involving the manipulation of trapping states through Cs2CO3 deposition is proposed to explain the resistive switching behavior of the memristive device.
CRIS-Team Scopus Importer:2025-04-11
Keywords: 2D layered Pb─Sn perovskite; analog CAM; neuromorphic computing; trap states

Overcoming optical losses in thin metal-based recombination layers for efficient n-i-p perovskite-organic tandem solar cells - Tian, Jingjing; Liu, Chao; Forberich, Karen; Barabash, Anastasia; Xie, Zhiqiang; Qiu, Shudi; Byun, Jiwon; Peng, Zijian; Zhang, Kaicheng; Du, Tian; Sathasivam, Sanjayan; Macdonald, Thomas J.; et al. (Nature Communications, 2025)
Perovskite-organic tandem solar cells (P-O-TSCs) hold substantial potential to surpass the theoretical efficiency limits of single-junction solar cells. However, their performance is hampered by non-ideal interconnection layers (ICLs). Especially in n-i-p configurations, the incorporation of metal nanoparticles negatively introduces serious parasitic absorption, which alleviates photon utilization in organic rear cell and decisively constrains the maximum photocurrent matching with front cell. Here, we demonstrate an efficient strategy to mitigate optical losses in Au-embedded ICLs by tailoring the shape and size distribution of Au nanoparticles via manipulating the underlying surface property. Achieving fewer, smaller, and more uniformly spherical Au nanoparticles significantly minimizes localized surface plasmon resonance absorption, while maintaining efficient electron-hole recombination within ICLs. Consequently, optimized P-O-TSCs combining CsPbI2Br with various organic cells benefit from a substantial current gain of >1.5 mA/cm2 in organic rear cells, achieving a champion efficiency of 25.34%. Meanwhile, optimized ICLs contribute to improved long-term device stability.
CRIS-Team Scopus Importer:2025-01-31

Polymer-acid-metal quasi-ohmic contact for stable perovskite solar cells beyond a 20,000-hour extrapolated lifetime - Luo, Junsheng; Liu, Bowen; Yin, Haomiao; Zhou, Xin; Wu, Mingjian; Shi, Hongyang; Zhang, Jiyun; Elia, Jack; Zhang, Kaicheng; Wu, Jianchang; Xie, Zhiqiang; Liu, Chao; et al. (Nature Communications, 2024)
The development of a robust quasi-ohmic contact with minimal resistance, good stability and cost-effectiveness is crucial for perovskite solar cells. We introduce a generic approach featuring a Lewis-acid layer sandwiched between dopant-free semicrystalline polymer and metal electrode in perovskite solar cells, resulting in an ideal quasi-ohmic contact even at elevated temperature up to 85 °C. The solubility of Lewis acid in alcohol facilitates nondestructive solution processing on top of polymer, which boosts hole injection from polymer into metal by two orders of magnitude. By integrating the polymer-acid-metal structure into solar cells, devices exhibit remarkable resilience, retaining 96% ± 3%, 96% ± 2% and 75% ± 7% of their initial efficiencies after continuous operation in nitrogen at 35 °C for 2212 h, 55 °C for 1650 h and 85 °C for 937 h, respectively. Leveraging the Arrhenius relation, we project an impressive T80 lifetime of 26,126 h at 30 °C.
CRIS-Team Scopus Importer:2024-03-15

Printing High-Quality Formanidinum Lead Triiodide Films: Understanding the Critical Role of α-Phase Nucleation Before Thermal Annealing - Qiu, Shudi; Dong, Lirong; Jang, Dongju; Yang, Fu; García Cerrillo, José; Li, Chaohui; Xie, Zhiqiang; Luo, Junsheng; Guo, Fei; Distler, Andreas; Du, Tian; Brabec, Christoph; et al. (Advanced Energy Materials, 2024)
Upscaling the coating of formamidinium lead triiodide (FAPbI3) thin film is essential to realizing full printing and thereby roll-to-roll production of perovskite photovoltaics. However, thin-film FAPbI3 processed from antisolvent-free, printing methods suffer from undesirable degradation to the non-photoactive phase, particularly in ambient processing conditions. Here, the most critical stage in thin-film processing is identified as the gas-quenching treatment of the as-cast wet film. It is crucial to achieve both the nucleation of α-phase nanocrystals and their sufficient growth at room temperature, which are indispensable for templating the growth of a highly crystalline and stable α-FAPbI3 film during subsequent thermal annealing. The gas-quenching-treated film without these α-phase nanocrystals can only be converted to meta-stable α-FAPbI3 by thermal annealing. By precisely identifying the spontaneous doping of cesium ion (Cs+) as a key factor in triggering α-FAPbI3 nucleation and the role of chloride ion (Cl−) in enhancing nanocrystal growth, a generalized mechanism for additive engineering for the precursor ink is theorized. The identified mechanism translates to a power conversion efficiency of 19.36% for fully printed carbon-electrode solar cells, 16.23% for carbon-electrode minimodules, and excellent operational stability, showing the promising potential of this proposed fabrication route in the upscaling of perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: carbon-electrode; cesium ion; FAPbI; nucleation; perovskite photovoltaics

Quantifying the Energy Losses in CsPbI2Br Perovskite Solar Cells with an Open-Circuit Voltage of up to 1.45 v - Tian, Jingjing; Zhang, Kaicheng; Xie, Zhiqiang; Peng, Zijian; Zhang, Jiyun; Osvet, Andres; Lüer, Larry; Kirchartz, Thomas; Rau, Uwe; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2022)
CsPbI2Br perovskite solar cells (PSCs) have attracted much interest because of their thermodynamic stability, relatively stable cubic perovskite phase, and their potential as a top cell for tandem applications. However, the open-circuit voltage (VOC) reported to date is in most cases well below the detailed balance (DB) limit for single-junction PSCs. Here, we demonstrate that adding lead acetate to the CsPbI2Br precursor allows us to substantially reduce losses due to nonradiative recombination. Corresponding champion devices reach a power conversion efficiency (-) of 16.7% and a highest VOC value of 1.45 V, which represents 90% of the DB limit for single-junction PSCs at a bandgap of 1.89 eV. In order to disentangle the nonradiative recombination loss mechanisms, we quantify the origin of energy losses by calculating the radiative limit of the open-circuit voltage (VOCrad) and the quasi-Fermi level splitting (QFLS) of perovskite films with and without other functional layers. We further analyze the strategies to reduce the residual losses in order to push the efficiency beyond the 90% theoretical limit.
CRIS-Team Scopus Importer:2022-11-18

Reducing Open-Circuit Voltage Losses in All-Inorganic Perovskite Cells by Dedoping - Peng, Zijian; Tian, Jingjing; Zhang, Kaicheng; These, Albert; Xie, Zhiqiang; Zhao, Yicheng; Osvet, Andres; Guo, Fei; Lüer, Larry; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2023)
CsPbI2Br is an attractive photovoltaic material due to its promising optoelectronic properties. However, the corresponding perovskite solar cells (PSCs) with p-i-n configuration suffer from low open-circuit voltage (VOC) and fill factor (FF), limiting their application in tandem solar cells. Here, we propose using the fullerene ICBA as the electron charge transporting layer (ETL), forming a better interfacial contact and enhancing the internal quasi-Fermi level splitting (QFLS). A further reduction of VOC losses of around 0.1 V was achieved by an ultrathin phenethylammonium chloride (PEACl) layer between the perovskite and the ETL. We precisely study the VOC improvement and find that passivation of surface recombination contributes only 20 mV, while more importantly, a major increase of 80 mV is achieved by dedoping the perovskite surface, which removes a non-negligible electron extraction barrier. Our results give helpful direction regarding how to further improve VOC in p-i-n perovskite cells.
CRIS-Team Scopus Importer:2023-04-21

Suppressing Nonradiative Recombination in Lead-Tin Perovskite Solar Cells through Bulk and Surface Passivation to Reduce Open Circuit Voltage Losses - Zhang, Kaicheng; Späth, Andreas; Almora, Osbel; Le Corre, Vincent Marc; Wortmann, Jonas; Zhang, Jiyun; Xie, Zhiqiang; Barabash, Anastasia; Hammer, Maria; Heumüller, Thomas; Min, Jie; Fink, Rainer; et al. (ACS Energy Letters, 2022)
Lead-Tin perovskite solar cells (Pb/Sn PSCs) are limited by the intrinsic instability of Sn(II), which tends to oxidize forming Sn vacancies in perovskite films. Herein, a Lewis base β-guanidinopropionic acid (GUA) and hydrazinium iodide (HAI) are introduced to effectively passivate the perovskite bulk and surface, respectively. The synergistic approach leads to Pb/Sn PSCs with a promising power conversion efficiency of 20.5% owing to the significantly reduced nonradiative recombination and voltage losses. As a result, the VOC × FF product of PSCs is significantly improved, which is among the highest values documented in the literature, being favorable for perovskite-based tandem applications. Additionally, the strategy demonstrated in this work could also improve the stability of PSCs by enhancing the chemical robustness of the perovskite layer. These results emphasize the significance of bulk and surface passivation in the development of efficient and stable PSCs based on Pb/Sn perovskites.
CRIS-Team Scopus Importer:2022-09-30

Tailoring the Dimensionality of 2D/3D Heterojunctions for Inverted Perovskite Solar Cells - Li, Chaohui; Zhang, Kaicheng; Maiti, Santanu; Peng, Zijian; Tian, Jingjing; Park, Hyoungwon; Byun, Jiwon; Xie, Zhiqiang; Dong, Lirong; Qiu, Shudi; Bornschlegl, Andreas; Liu, Chao; et al. (ACS Energy Letters, 2024)
Interface engineering is crucial to achieving stable perovskite photovoltaic devices. A versatile approach is developed to tailor interface properties via integrating co-assembled monolayers (co-SAMs) at the p-type buried interface and by capping a two-dimensional (2D) perovskite layer at the n-type upper interface with vacuum quenching. Optimized co-SAMs promote the coverage of the hole transport layer, significantly reducing the incidence of leakage currents. Based on this foundation, we develop damp-heat-stable perovskite solar cells by precisely tailoring the fragments of 2D perovskite layers through vacuum annealing with phenethylammonium iodide. An impressive open-circuit voltage of 1.216 V is achieved, corresponding to 92% of the value determined by the detailed-balance limit, along with a power conversion efficiency of 23.68%. Ultimately, integrating co-SAMs and the vacuum-assisted annealing fabricated devices maintain 96% and 80% of initial efficiencies after 1200 and 500 h of tracking at a maximum power point under 55 and 85 °C, respectively.
CRIS-Team Scopus Importer:2024-02-23

Unraveling Dual Operational Mechanisms in an Air-Stable All Inorganic Perovskite for Nonvolatile Memory and Neuromorphic Computing - Xie, Zhiqiang; Zhang, Difei; Cheng, Long; Li, Chaohui; Elia, Jack; Wu, Jianchang; Tian, Jingjing; Chen, Lijun; Loi, Maria Antonietta; Osvet, Andres; Brabec, Christoph (ACS Energy Letters, 2024)
Two-terminal drift memristors (nonvolatile) are widely employed to emulate biological synaptic functionalities in neuromorphic architectures. However, reliable emulations of synaptic dynamics can only be achieved through the integration of their counterparts, diffusive memristors. Moreover, the combination of drift and diffusive memristors represents a desirable approach to address the escalating demands posed by the increasing complexity of neuromorphic computing frameworks, which are still in their nascent stages. Accordingly, an air-stable inorganic perovskite memristor (RbPbI3) is demonstrated with adjustable drift and diffusive modes. By employing an electroforming process, the drift-type devices demonstrate bipolar resistive switching with a large ON/OFF ratio (102), stable endurance (2000 cycles), long retention (1.2 × 105 s), and robust air stability. In contrast, diffusive-type devices, without an electroforming process, effectively emulate synaptic behaviors, including paired-pulse facilitation, long-term potentiation/depression, and spike-timing-dependent plasticity. Additionally, experimental data are utilized to train neural networks constructed with perovskite artificial synapses on image classification tasks. The results demonstrate accuracies of 89.24% (MNIST) and 79.10% (Fashion-MNIST) under supervised learning, closely approximating their theoretical values.
CRIS-Team Scopus Importer:2024-03-01